Foundations of human resource development - Swanson, Richard A. 1942- (Berrett-Koehler Publishers, Inc., 2022)
"Human resource development (HRD) is a large field of practice but a relatively young academic discipline. For the last two decades, Foundations of Human Resource Development has fulfilled the field's need for a complete and thoughtful foundational text. This essential text provides an up-to-date overview of the HRD profession, along with the terminology and processes required for sound HRD research and practice. Readers will gain a basic understanding of HRD models and theories that support best practice. The history and philosophical foundations of the field. HRD's role in learning, performance, and change in organizations This new edition has been updated throughout and contains new chapters on assessment, technology, globalization, and future challenges. Examples of best practices are included, along with variations in core thinking, processes, interventions, tools, and much more. This must-have reference will help both practitioners and academics add clarity to their professional journeys"--
Revised edition of Foundations of human resource development, c2009
Keywords: Employees / Training of; Personnel management; Manpower planning; Human capital; Inservice Training; Personnel Management; Personnel / Formation; Personnel / Direction; Main-d'uvre / Planification